Clever Cooperation: Interactions Between EspF and Host Proteins - Hua, Ying; Yan, Kaina; Wan, Chengsong (Frontiers in Microbiology, 2018)
EspF is a central effector protein of enterohemorrhagic Escherichia coli (EHEC), enteropathogenic E. coli (EPEC), and Citrobacter rodentium (CR) that is secreted through the type III secretion system to host cells. The interaction between EspF and host proteins plays an important role in bacterial pathogenesis. EspF protein binds to host SNX9 and N-WASP proteins to promote the colonization of pathogenic bacteria in intestinal epithelial cells; combines with cytokeratin 18, actin, 14-3-3ζ, Arp2/3, profilin, and ZO-1 proteins to intervene in the redistribution of intermediate filaments, the rearrangement of actin, and the disruption of tight junctions; acts together with Abcf2 to boost host cell intrinsic apoptosis; and collaborates with Anxa6 protein to inhibit phagocytosis. The interaction between EspF and host proteins is key to the pathogenic mechanism of EHEC and EPEC. Here, we review how EspF protein functions through interactions with these 10 host proteins and contributes to the pathogenicity of EHEC/EPEC.